Correlation between Milk Production Traits, Certain Hormones and Serum Biochemical Parameters in Lactating Murrah Buffaloes - Bahiram, K.B.; Khan, J.R.; Korde, J.P. (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
The objective of the study was to evaluate correlation between milk yield (MY), milk components (fat, protein and lactose), hormones (T3, T4, insulin and GH), blood metabolites (glucose and NEFA) and blood macro-minerals (Ca, P and Mg) during entire lactation based on 161 observations of 07 Murrah buffaloes. The average Lactation length recorded was 338.57 ± 10.64 days. The correlations between MY and milk composition, hormones with MY and milk composition, blood metabolites with MY and milk composition and blood macro-minerals values with MY and milk composition during the entire lactation were evaluated. The results indicated that the relationship of blood hormones, energy metabolites and blood macro-minerals parameters would help to understand the role of each of them in understanding the lactational physiology of buffaloes in relation to endocrine regulation and nutritional partitioning.